An Analysis of Types of Taboo Words in Parker Movie - Sari, Yunita Permata (Humanis; Vol 24 No 3 (2020), 2020)
This research focuses on types of taboo words that used in Parker movie. This research is a qualitative research. The data of this research were taken from Parker movie. Data were collected by using an observation method and non- participant technique (Sudaryanto,2015) . The data are analyzed using the pragmatic identity method (Sudaryanto, 2015). In analyzing the data, the researchers applying Battistella (2005) theory. The result of this research was presented using an informal method.The researcher found out three types of taboo word that appeared in Parker Movie. There are obscenity types, profanity types, and epithet types. Obscenity is the type with the highest number of occurrences, followed profanity type after that. Then, the least number of occurences is epithet type.